2007
DOI: 10.1016/s0828-282x(07)70227-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nebivolol on fibrinolytic parameters in mild and moderate hypertensive patients

Abstract: T he vascular endothelium is a metabolically active paracrine organ. It regulates thrombogenicity, vascular tone, leukocyte adhesion, and platelet and smooth muscle function (1). While normal endothelium is in a nonthrombotic state, deterioration of the vascular endothelium results in the synthesis and release of procoagulant and anticoagulant substances from the disrupted vascular endothelium (2,3).One of the major risk factors for atherosclerosis is hypertension. Most of the studies on hypertensive subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
2
8
0
2
Order By: Relevance
“…IL-6 is a cytokine that functions in both innate and adaptive immunity and is also responsible for many of inflammatory responses. Moreover, both TNF-␣ and IL-6 are involved in the inflammatory response occurring in vascular endothelial and promote the initiation and evolution of atherosclerosis by causing endothelial cells to express adhesion molecules and induced endothelial dysfunctions (Ridker et al, 2000;Verma et al, 2002;Tarighi et al, 2007). Here, we observed that mSMS extract could remarkably suppress the production of inflammatory cytokines, including TNF-␣ and IL-6 from LPS-activated RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 61%
“…IL-6 is a cytokine that functions in both innate and adaptive immunity and is also responsible for many of inflammatory responses. Moreover, both TNF-␣ and IL-6 are involved in the inflammatory response occurring in vascular endothelial and promote the initiation and evolution of atherosclerosis by causing endothelial cells to express adhesion molecules and induced endothelial dysfunctions (Ridker et al, 2000;Verma et al, 2002;Tarighi et al, 2007). Here, we observed that mSMS extract could remarkably suppress the production of inflammatory cytokines, including TNF-␣ and IL-6 from LPS-activated RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 61%
“…In an uncontrolled study in hypertensive patients, nebivolol decreased the PAI-1/t-PA ratio but did not affect PAI-1 antigen or activity concentrations. 29 Vyssoulis et al reported that nebivolol and celiprolol reduced PAI-1 whereas carvedilol did not in patients with uncomplicated hypertension; however, twenty percent of patients were also taking hydrochlorothiazide, which increases PAI-1. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Treatment trial in patients in the early stage of 324 hypertension with nebivolol was associated with a more favour-325 able modification of haemostatic and fibrinolytic status in addition 326 to antihypertensive effects [96]. Nebivolol decreased fibrinogen, 327…”
mentioning
confidence: 99%